Crown-bit elektroozonator for continuous disinfection of eggs in incubators - Barhatov, A.; Kovalchuk, I.; Rumyantsev, O. Rumyantsev; Slivka, Y.; Popov, A. (Energy and Automation, 2015)
The recommendations for engineering calculations and design parameters for the system elektroozonatoriv ozone ambient air incubator.